CFTR and Ca2+ Signaling in Cystic Fibrosis - Antigny, Fabrice; Norez, Caroline; Becq, Frederic; Vandebrouck, Clarisse (Frontiers in Pharmacology, 2011)
Among the diverse physiological functions exerted by calcium signaling in living cells, its role in the regulation of protein biogenesis and trafficking remains incompletely understood. In cystic fibrosis (CF) disease the most common CFTR (Cystic Fibrosis Transmembrane conductance Regulator) mutation, F508del-CFTR generates a misprocessed protein that is abnormally retained in the endoplasmic reticulum (ER) compartment, rapidly degraded by the ubiquitine/proteasome pathway and hence absent at the plasma membrane of CF epithelial cells. Recent studies have demonstrated that intracellular calcium signals consequent to activation of apical G protein-coupled receptors (GPCRs) by different agonists are increased in CF airway epithelia. Moreover, the regulation of various intracellular calcium storage compartments, such as ER is also abnormal in CF cells. Although the molecular mechanism to explain this increase remains puzzling in epithelial cells, the F508del-CFTR mutation is proposed to be the origin of abnormal Ca2+ influx linking the calcium signaling to CFTR pathobiology. This article reviews the relationships between CFTR and calcium signaling in the context of the genetic disease cystic fibrosis.